1996
DOI: 10.1063/1.472737
|View full text |Cite
|
Sign up to set email alerts
|

Coriolis-dependent Stark effect of the 2ν3 band of methane observed by saturated absorption spectroscopy

Abstract: We studied the vibration-induced dipole moment of methane by observing Stark-modulation spectra of the 2ν3 band centered at 1.66 μm. The spectral purity of an external cavity semiconductor laser and radiation density in a Fabry–Perot cavity absorption cell are sufficiently high to record sub-Doppler saturated absorption lines with a spectral resolution of 0.8 MHz. First-order Stark shifts of the E-type symmetry components in the P(2), Q(2), Q(4), Q(5), R(2), R(4), and R(5) transitions were measured, and the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…65,66 To the best of our knowledge, the first measurements of sub-Doppler saturated absorption (Lamb dips) in the 2n 3 band of methane were reported in the 1990s by the group of Sasada of Keio University in Yokohama (Japan). [68][69][70] Optical frequency combs were not available at that time and precise frequency differences between 2n 3 transitions were obtained as the optical beat frequency between two external-cavity diode lasers locked at 1 MHz-wide saturated absorption dips of the methane lines. A number of frequency differences mostly between Q-branch transitions of the 2n 3 band were reported with a precision better than 40 kHz.…”
Section: Literature Reviewmentioning
confidence: 99%
“…65,66 To the best of our knowledge, the first measurements of sub-Doppler saturated absorption (Lamb dips) in the 2n 3 band of methane were reported in the 1990s by the group of Sasada of Keio University in Yokohama (Japan). [68][69][70] Optical frequency combs were not available at that time and precise frequency differences between 2n 3 transitions were obtained as the optical beat frequency between two external-cavity diode lasers locked at 1 MHz-wide saturated absorption dips of the methane lines. A number of frequency differences mostly between Q-branch transitions of the 2n 3 band were reported with a precision better than 40 kHz.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first two mechanisms were theoretically predicted by Mizushima and Venkateswarlu The molecule-fixed PDM m a can be expanded in the usual way (2-5, 8, 13, 14, 17) into a series of terms which are the (2), and by Watson (3), Fox (4), and Aliev (5), and were experimentally verified by Uehara et al (6) and Ozier (7) products of the dimensionless normal coordinate operator q ta , the dimensionless total angular momentum operator J a , and more than 20 years ago. Very recently the last mechanism, proposed by Aliev et al (8), was confirmed in sub-Doppler the dimensionless vibrational angular momentum operator l ta Å (q tb p tg 0 q tg p tb ), where a Å x, y, z are the S 4 axes, p ta resolution spectroscopy of the 2n 3 band of methane (9).…”
Section: Theorymentioning
confidence: 93%
“…Fox ( 26 ) attributed the similarity to the facts that vibrational state. This set of the PDMs has been used in the anharmonicity separates the degenerate vibrational state the previous experimental works ( 9,25 ) for the analysis of the Stark effects.…”
mentioning
confidence: 99%
“…Another frequency modulation is applied to NICE-OHMS by the EOM at 478.5 MHz, which is equal to the FSR of the FP cell, and the modulation index is 0.092, which is limited by the small gain of the rf-amplifier used. A sawtooth voltage is applied to the PZT to sweep the frequency of the cavity mode, while the laser frequency follows it through the fre-sitivity of the previous spectrometers [6][7][8][9][10][11][12][13] does not induce any noise in the FM signal. They observed overtone transitions of C 2 HD, C 2 H 2 , and CO 2 with a stable 1.064 µm Nd : YAG laser 16) and obtained a spectral resolution of 70 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…7-10) Following them, Suzumura and co-workers observed the saturation spectrum of the 2ν 3 band of methane in the 1.66 µm region, 11) and conducted sub-Doppler resolution spectroscopy. 12,13) The technique [6][7][8][9][10] is also sensitive because of its large absorption length. However, even a small frequency difference between the laser and the cavity mode is converted into a large amplitude noise of the radiation intensity transmitted through the FP cell because the high-finesse cavity works as a sensitive frequency discriminator.…”
Section: Introductionmentioning
confidence: 99%